Use of cadastral databases in land consolidation in Poland - Konieczna, Jadwiga; Trystuła, Agnieszka (International Conference “Environmental Engineering”, 2017)
Land consolidation in the European Union is not only a tool used to improve the economy of rural areas. When setting goals for land consolidation, one should take into account the social and environmental aspects. The socio cultural needs related to use of natural resources of rural landscape, cultural heritage, agritourism or technical infrastructure are as important as the profit earned by farms; they also help to maintain the harmony with the natural environment. For land consolidation to play a significant role in developing a strategy of multifunctional and sustainable development of rural areas, those who carry it out must have free access to up o ate and properly selected databases; a cadaster of real property could be one of the sources of such data. A real estate cadaster is a public register, which provides credible identification of plots in a specific space. It is possible because when gathering information about land, buildings, apartments as well about their owners and holders, the system ensures its topicality, which is a priority despite the ever changing space around us. The aim of the study is to present the significant role of cadastral databases in land consolidation as they help to develop the optimum relations between the economy, rural areas, communities and environmental protection.